1997
DOI: 10.1038/bjc.1997.245
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of tumour-infiltrating lymphocytes to endothelium: a phenotypic and functional analysis

Abstract: Summary Efficacy of cancer immunotherapy with cultured tumour-infiltrating lymphocytes (TlLs) depends upon infused TILs migrating into tumour-bearing tissue, in which they mediate an anti-tumour response. For TILs to enter a tumour, they must first bind to tumour endothelium, and this process depends on TILs expressing and regulating the function of relevant cell-surface receptors. We analysed the cell-surface phenotype and endothelial binding of TILs cultured from human melanoma and compared them with periphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

1998
1998
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 62 publications
1
16
0
1
Order By: Relevance
“…The molecule was appropriately expressed on an endothelial cell line. Lack of expression on TIL is consistent with our previous published work showing a lack of avb3 on TIL isolated from malignant melanoma (Adams et al, 1997). Other integrins that can bind vitronectin are not found at high levels on lymphocytes (Nejjari et al, 2002), but the uPAR, which can either modulate the function of other integrins or act directly as an adhesion receptor for vitronectin has been demonstrated on activated lymphocytes and reported to mediate migration (Nykjaer et al, 1994;Wei et al, 1994;Bianchi et al, 1996;Blasi, 1997).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The molecule was appropriately expressed on an endothelial cell line. Lack of expression on TIL is consistent with our previous published work showing a lack of avb3 on TIL isolated from malignant melanoma (Adams et al, 1997). Other integrins that can bind vitronectin are not found at high levels on lymphocytes (Nejjari et al, 2002), but the uPAR, which can either modulate the function of other integrins or act directly as an adhesion receptor for vitronectin has been demonstrated on activated lymphocytes and reported to mediate migration (Nykjaer et al, 1994;Wei et al, 1994;Bianchi et al, 1996;Blasi, 1997).…”
Section: Discussionsupporting
confidence: 79%
“…FACS was used to phenotype TIL, PBL and the dermal microvascular endothelial cell line HMEC-1 (a gift of Dr E Ades (CDC Atlanta, GA, USA)) (Adams et al, 1997). HMEC-1 were grown as described before.…”
Section: Flow Cytometrymentioning
confidence: 99%
“…6 However, such treatments are only successful if infused lymphocytes are recruited to and retained within the tumor. 6,22,61 The importance of local chemokines in antitumor immune responses is confirmed by studies that show increased T-cell responses against tumor cells transfected with genes for lymphocyte chemokines. 62 We have shown previously that HCC, but not colorectal hepatic metastases, contain the appropriate endothelial adhesion molecules to support lymphocyte recruitment, 10 HEPATOLOGY Vol.…”
Section: Table 2 C-c and C-x-c Chemokine Expression In Normal Livermentioning
confidence: 64%
“…16,21 Thus, lymphocytes will only be recruited to tissue if they express the appropriate receptors that allow them to respond to locally presented chemokines within tissue. 14 Because lymphocyte adhesion to tumor endothelium appears to be regulated by similar mechanisms, 20,22 it is likely that chemokine/chemokine receptor interactions will also be crucial for the recruitment of lymphocytes to tumors.…”
mentioning
confidence: 99%
“…The binding molecules for ICAM-1 in neutrophils and monocytes are the integrin ligands LFA-1 and Mac-1 [40]. De novo expression of ICAM-1 has been described on different cell types in inflammatory lesion during rejection, and on melanoma cells [41]. Experimental studies have also shown that antibodies against ICAM-1 inhibit leukocyte adhesion to endothelial cells, granulocyte migration through endothelium, and mixed lymphocyte reactions in vitro [42].…”
Section: Discussionmentioning
confidence: 99%